On the system of deducting a "Per-centage" from the purchase money of estates sold with Parliamentary Title, with a view to the abolition of fees in Chancery - Wrenfordsley, Henry (Dublin Statistical Society, 1857)
A Bill was prepared in the early part of last year to alter the constitution, procedure and practice, to increase the powers, and diminish the expense of in the Court of Chancery in Ireland and to discontinue the Incumbered Estates' Court. The Bill also provided that a percentage of purchase money should be paid out proceeds of the estates or leases sold under the increased jurisdiction which it was then proposed to give the Court of Chancery. It is to this portion of the bill that I purpose applying the present observations, with the view of seeing how far the scheme has been sanctioned by subsequent enquiry.
Read Tuesday, 28th April, 1857
Keywords: Incumbered estates; Land purchase; 314.15